Compassion focused therapy participant workbook - Arnold, Rachel (New York, NY : Routledge, 2022)
Compassion Focused Therapy Participant Workbook is a companion book to Compassion Focused Group Therapy for University Counseling Centers, a one-of-a-kind 12-session manual for conducting compassion focused group therapy on college campuses. Compassion-based interventions have been shown to decrease symptoms of depression, anxiety, and psychological distress in students. This book's 12 sessions incorporate several aspects of compassionate living including defining and understanding compassion, mindfulness, shame, assertiveness, and forgiveness to help participants act in more compassionate ways with themselves and others, lower feelings of shame and self-criticism, and engage in self-reassuring behaviors. The workbook provides clients with summaries of each session, handouts, and key exercises and, along with the manual, can be followed session-by-session or adapted according to the needs of the group. This workbook is designed to be used by clinicians and participants in a clinician-led group utilizing Compassion Focused Group Therapy for University Counseling Centers.
Includes index.
Keywords: College students -- Mental health; Emotion-focused therapy; Compassion; PSYCHOLOGY / Psychotherapy / Group